Brief Report: HIV Infection Does Not Explain Higher Nicotine Metabolism in People Living With HIV. (15th December 2022) - Arens, Yotam; Bilker, Warren B.; Han, Xiaoyan; Plankey, Michael; Ware, Deanna; Friedman, M. Reuel; D'Souza, Gypsyamber; Stosor, Valentina; Shoptaw, Steven; Schnoll, Robert A.; Tyndale, Rachel F.; Ashare, Rebecca; et al.
Abstract : Background: Smoking contributes to significant morbidity and mortality in people with HIV. People with HIV have relatively high nicotine metabolism rates, as measured by the nicotine metabolite ratio (NMR, 3-hydroxycotinine/cotinine). A higher NMR is associated with difficulty quitting smoking. We hypothesized that HIV infection might upregulate nicotine metabolism. Setting: A retrospective study of male current smokers in the Multicenter AIDS Cohort Study who HIV seroconverted between 1985 and 1993. Methods: Eligibility included having plasma stored before and after confirmed HIV seroconversion and current tobacco use. Samples were selected from the closest available visits before (median 3.3 months) and after (median 9.4 months) seroconversion. Antiretroviral therapy use was exclusionary. Cotinine and 3-hydroxycotinine were measured using liquid chromatography–tandem mass spectrometry. We compared NMR from plasma pre-HIV and post-HIV infection using signed-rank tests. We targeted a sample size of 71 pairs to achieve 80% power to detect a 0.1 unit increase in NMR with P = 0.05. Results: We analyzed paired samples from 78 participants; the median age was 34.5 years [interquartile range (IQR 29–40 years)]. The median NMR pre-HIV and post-HIV was 0.45 (IQR 0.32–0.54) and 0.46 (IQR 0.34–0.56), respectively. The median change in NMR postseroconversion was +0.01 (IQR −0.05, +0.09), P = 0.25. Stratification of median change in NMR by timing between samples or time since HIV seroconversion did not alter this finding. Conclusions: Acquiring HIV had no measurable effect on NMR. We postulate that upregulation of the NMR may be due to direct pharmacologic effects of HIV medications or metabolic changes in response to HIV infection.